The Correlation Between Degree of Orthodontic Treatment Knowledge and Obedient of Maintain Self the Fixed Orthodontic Patient - Fahma Widya Kusumawardhani (Jurnal Kesehatan Gigi, 2020)
Based on the result of a preliminary study conducted at one of the dentist practice in Yogyakarta with interviewing patient and seeing the medical record of 10 people who using a fixed orthodontic, the data obtained 7 people have high knowledge about orthodontic treatment and 3 people haven’t. This study aims to knowing the relationship between degree of orthodontic treatment knowledge and obedient of maintain self the fixed orthodontic patient. The type of research is analytics with research design is cross sectional. The samples taken all of samples who including criteria the patient using fixed orthodontic on maxilla and/or mandible, age 15-45 years old, want to be the respondent and answer the questioner with the amount is 38 people. The variable of the research consist of influence variable is degree of orthodontic treatment knowledge using ordinal scale and variables affected is obedient of maintain self the fixed orthodontic using nominal scale. Analysis of the data using Chi-square. The result showed that the degree of orthodontic treatment knowledge high is 19 (50%), moderate knowledge is 13 (34,2%) and the low knowledge is 6 people (15,8%). While the result of obedient of maintain self with obey criteria is 22 (57,9%) and do not obey is 16 people (42,1%). The result of chi-square between 2 variable is the count of X2 is 6,214 while chi-square value X2 on the table with level of the significance 0,05 is 5,591. This result means the count X2 X2on the table, the conclusion is Ho is rejected and Ha is accepted. So there are a correlation between degree of orthodontic treatment knowledge and obedient of maintain self the fixed orthodontic patient.